Investigating Kalmykia’s Governance Arrangements, Mid-to-Late Nineteenth Century: Documents of Horde [Affairs] Department at Astrakhan Chamber of State Property (1848–1867) as a Historical Source - Larisa B. Mandzhikova (Oriental Studies)
Introduction. The mid-to-late nineteenth century was witnessing further integration of Kalmyk Steppe and its society into the Russian state system. During the period under review, it was the Horde [Affairs] Department at Astrakhan Chamber of State Property (1848–1881) that became in charge of the administrative reform, with activities guided by the Kalmyk People’s Governance Regulations of 23 April 1847. The agency’s documents had compiled Collection И-6 (‘Horde [Affairs] Department at Astrakhan Chamber of State Property, 1832–1881’) at the National Archive of Kalmykia. Goals. The study seeks to investigate the reference apparatus to Collection И-6, analyze its structure and types of documents, identify common and distinctive features in record keeping at the newly created government body after the introduction of the 1847 Regulations, and the former’s source potential for historical research of state institutions in prerevolutionary Kalmykia. Results. The Regulations of 1847 established a clear division of powers between the Governor’s Office and Kalmyk elites, and sought to articulate certain division of powers in Kalmyk self-governance too. The Regulations specified directions of activity for structural units of the Horde [Affairs] Department, which had its impacts on workflow management essentials of the Kalmyk people’s governing body. The documents that resulted from the latter’s activities are related to official record keeping and their formatting patterns meet the requirements of that era. The archival documents included in Collection И-6 are a valuable source for further historical insights into how local public institutions in Russia would develop throughout the prerevolutionary period, and how Kalmykia’s administrative structures would evolutionize accordingly.